Photocatalytic Properties of TiO2 Coated SiO2 Particles by Metal Alkoxide Processing - Yokota, Toshiyuki; Ohwada, Hiroto (KAGAKU KOGAKU RONBUNSHU, 1995)
Semiconductor photocatalysts of TiO2/SiO2 composite particles were prepared by hydrolysis of titanium isopropoxide. The hydrolysis was performed in an ethyl alcohol solution in which spherical silica particles of micron order dimensions were supplied as a substrate for TiO2 deposion. A sub-micron meters TiO2 layer was observed on the particle surface. These TiO2-coated silica particles were heat treated to form an anatase or a rutile crystal phase of TiO2. The photo-electrochemical deposition method was adopted to generate platinum metal dots on the TiO2. surface. The photocatalytic activity of the particles was assessed by photo-decomposition of methyl alcohol in aqueous solution. The results of decomposition showed that anatase type TiO2 of 0.25 μm thickness containing 0.75 wt% of deposited platinum exhibited sufficient activity. Separation of the suspended catalyst particles was easily achieved by simple filtration after the reaction. Therefore, this catalyst may be suitable for practical usage in large scale industrial operations.